The Coffee Shop Influence on Coffee Consumption in the City of Sao Paulo - Nassif, Wander; Rossi, George Bedineli; Garcia, Mauro Neves; Bazanini, Roberto (Review of Business Management, 2007)
Coffee is a product of high national demand and has been present in the consumer habits, indicating a great search for distinguished and quality coffees. The evaluations of this product are based on descriptive and deductive positions, also on its own information. The perceived characteristics can be intrinsic such as the taste, aroma, color, appearance and consistency or extrinsic which refers to the outer part that surrounds the product such as the environment, packaging, brand and also the country of origin. This study is aimed at examining whether intrinsic and extrinsic characteristics of coffee drink stimulate the consumer to attend coffee shops (specialized environment for consuming coffee). For such, an exploratory survey was made, using field and bibliographical researches whose results were dealt by the content analysis. One of the instruments to collect data was a program of interviews with 87 people, who regularly attend coffee shops. The specific places are located in Sao Paulo (two of them at a mall in the Higienópolis neighborhood and the other one is at an University campus in the center of the city). The results show that the interviewees considered first the coffee taste, and then the coffee aroma as the most significant intrinsic characteristics. Nevertheless, they recognized value in a pleasant, comfortable and refined environment. Both characteristics have been complementary and the quoted factors were Coffee is a product of high national demand and has been present in the consumer habits indicating a great search for distinguished and quality coffees. The evaluations of this product are based on descriptive and deductive positions, also on its own information. The perceived characteristics can be intrinsic such as the taste, aroma, color, appearance and consistency or extrinsic which refers to the outer part that surrounds the product such as the environment, packaging, brand and also the country of origin. This study is aimed at examining whether intrinsic and extrinsic characteristics of coffee drink stimulate the consumer to attend coffee shops (specialized environment for consuming coffee). For such, an exploratory survey was made, using field and bibliographical researches whose results were dealt by the content analysis. One of the instruments to collect data was a program of interviews with 87 people, who regularly attend coffee shops. The specific places are located in Sao Paulo (two of them at a mall in the Higienópolis neighborhood and the other one is located at a University campus in the center of the city). The results show that the interviewees considered first the coffee taste, and then the coffee aroma as the most significant intrinsic characteristics. Nevertheless, they recognized value in a pleasant, comfortable and refined environment. Both characteristics have been complementary and the quoted factors were mentioned as the ones who stimulate the consumer to attend coffee shops. Key-words: Coffee shops. Coffee consumption. Service marketing. Consumer Behavior.